Japan's policy and views on nuclear weapon: a historical perspective2 - Katsuhisa Furukawa1, (Penerbit UKM, 2010)
This article discusses the history of Japan’s pursuit of its nuclear policy and views on nuclear weapons since the Second World War. It explains how Japan’s strategic thinking on nuclear weapons changed in accordance with changing security environment over the past decades, and the details of Japan’s past examinations of its nuclear option as well as Japan’s efforts to sustain and strengthen credible deterrence and policy on nuclear nonproliferation, disarmament, and arms control. The article concludes that the likelihood for Japan to go nuclear seems extremely low as long as the current trend in the security environment may not experience significant transformation. Instead, Japan will continue to strengthen its alliance with the United States and overall deterrence posture while pursuing nuclear nonproliferation, disarmament, and arms control together with the international community, especially with the countries in East Asia. This article also argues that Japan’s focus on nuclear option should not be seen as undermining the security and stability of Asia, but rather that it is a prerequisite, in a way, to foster healthy discussion over security policy in Japan, and to strengthen the Japan-U.S. alliance, to prepare for new security challenges in evolving strategic environment in this region.